Conformal Radiotherapy for Squamous Cell Carcinoma of Gallbladder: A Case Report - Jia-zhou Hou; Zhao-chong Zeng; Jing Sun; Yuan Ji (Case Reports in Medicine)
Background. Squamous cell carcinoma of the gallbladder is a rare disease with symptoms developing late in its course, so that it often presents as an aggressive tumor with a poor prognosis. Case report. We describe a 58-year-old male with a 5-week history of hypodynamia. He was found to have squamous cell carcinoma of the gallbladder with liver invasion and lymph node metastases. He underwent treatment with 3-dimensional conformal radiation therapy (CRT). A follow-up computer tomography (CT) scan showed complete tumor remission 2 months after the completion of CRT. The patient survived for 14 months after the end of treatment and died of multiple liver metastases. Conclusion. The efficacy of radiotherapy in this case is encouraging and suggests a potential role for such therapy in similar cases. The benefit in terms of survival warrants further study.